EXPANSÃO DO INSTITUTO FEDERAL DE SANTA CATARINA: A IMPLANTAÇÃO DO CAMPUS GAROPABA E SUA RELAÇÃO COM O MERCADO - Tiago Savi Mondo (Universidade Federal de Santa Catarina, 2011)
The expansion at the Federal Institute of Santa Catarina is reality, where the three campuses now has 19 campuses. And Campus Garopaba is one that is under construction. The difficulties are great partnership with him to market the region's basic assumption for the success of this deployment. Thus, the purpose of this paper is to examine the mechanisms of relationship and communication with the market occurring in the process of implementation of the Campus Garopaba of Federal Institute of Santa Catarina from research participant. The study is characterized as exploratory and descriptive type case report. Survey was conducted participant observation for a description of activities on campus. The results show that the mechanisms Campus uses print, radio, meetings with authorities and associations and the Internet and digital media. It is considered important initiatives of relationship and communication in the process of return, thereby carrying out a collective construction, together with the community.